Karakteristik Disturbansi di Rentang Frekuensi 9-150 kHz Pada Sistem UPS Berbeban Induktif - Rheo Loridho Pratama; Budi Sudiarto (CIRCUIT: Jurnal Ilmiah Pendidikan Teknik Elektro, 2020)
In every UPS device there are power electronic components including inverters, therefore using an inverter will cause voltage disturbances at high frequency because the switching frequency of the inverter is at high frequency. Data recorded by the oscilloscope along with the Picolog Recorder software and processed by  Matlab software to make it more efficient. Research conducted when the UPS uses dual conversion mode and with inductive load variations 0.35 H, 0.7 H, 1.4 H and 2.8 H. The test results show that voltage disturbances occur in three dominant frequency ranges at each level of load variations are 9-19 kHz, 20-30 kHz and 31-41 kHz. In the condition of 10% loading rate with a load of 0.35 H the peak voltage disturbances occur at 81.17 mV in frequency of 9.2 kHz and at the condition of the 75% loading rate with 2.8 H load the peak voltage disturbances that occur at 92.20 mV in frequency of 9.6 kHz. The disturbances voltage increases with the increasing of  inductive loads that connected to UPS.